Sunrise and Stormclouds - Edited by Morgan, Roger (London Readers' Digest Association, 1975)
Traces milestones on history from the aviation triumphs of the Wright brothers in 1903 to the Spanish civil war of 1936.
Include Index and Illustration
Keywords: History, Modern -- Civilization, Modern